Speculative trade under unawareness: The infinite case - Martin Meier; Burkhard C. Schipper (University of California, Department of Economics, 2014)
We generalize the "No-speculative-trade" theorem for finite unawareness belief structures in Heifetz, Meier, and Schipper (2013) to the infinite case.
Keywords: C70; C72; D53; D80; D82; D84; 330; awareness; unawareness; speculation; trade; agreement; common prior; common certainty